Assessment of responsiveness and minimum important difference of the Maternal perception of Childbirth Fatigue Questionnaire (MCFQ) - Delgado, Alexandre; Góes, Paulo Sávio Angeiras de; Lemos, Andrea (ABCS Health Sciences, 2022)
Introduction: The assessment of responsiveness and the Minimum Clinically Important Difference (MCID) is the basis for validating the Maternal perception of Childbirth Fatigue Questionnaire (MCFQ). Objective: To assess the responsiveness and determine the value of the MCID for the MCFQ. Methods: This is an observational study, conducted at HC-UFPE with 50 parturients in active labor. The MCFQ was applied in two moments: in the initial evaluation (EV1), performed at the beginning of labor between 4-6 cm of uterine dilation, and final (EV2), six hours after the first evaluation. Responsiveness was determined by calculating the effect size (ES), and standardized response mean (SRM), considering that values of 0.2, 0.5, and 0.8 points represent respectively small, moderate, or large values of responsiveness. The ability to detect change through the questionnaire was also assessed by the t-test. The level of significance adopted for this analysis was p less than 0.05. The MCID was verified based on the calculation of the standard error of measurement (SEM) index. Results: The MCFQ showed values of 0.4 and 0.6 for ES and SEM respectively and a p-value <0.001, thus showing a good capacity for change. The value of the MCID for this population was seven points. Conclusion: MCFQ presents a potentially significant change with a value of the MCID of seven points after six hours of active labor.